Isolation and characterization of total volatile components from leaves of citrus limon linn. - Kadambari Tomer; Neeraj K Sethiya; Abhilasha Shete; Vijendra Singh (Wolters Kluwer Medknow Publications, 2010)
The isolation of the essential oil of whole fresh leaves of Citrus lemon by steam distillation is described. The chemical composition of the oil was investigated by means of Gas-Liquid Chromatography (GLC), Column Chromatography (CC) and coupled Gas Chromatography-Mass Spectrometry (GC-MS). The 27 most important volatile components were identified. The volatile components were identified by comparing their retention times of GC chromatograph with those of literature. Further identification was done by GC- MS. The components of the oil, percentage of each constituent, their RI values and their Eight Peak Index were also summarized and reviewed with standard available literature.